Keanekaragaman Semut pada Persawahan di Daerah Urban: Investigasi Pengaruh Habitat Sekitar dan Perbedaan Umur Tanaman Padi - ENRI AGUS SETIANI; AKHMAD RIZALI; MOERFIAH MOERFIAH; BANDUNG SAHARI; DAMAYANTI BUCHORI (Jurnal Entomologi Indonesia, 2010)
Agricultural intensification cause negative effect to insect diversity including beneficial insect such as natural enemies and pollinators. Habitat management through habitat heterogeneity is an alternative approach to protect insect diversity in agriculture area. In this study, we investigated the effect of habitat heterogeneity integrated with different age of crop plant in urban agricultural landscape to the ant diversity. The field research was conducted in agricultural area in Carang Pulang Village, Dramaga, Bogor. In around 6 ha area of rice field, grouped into four blocks which each block has different habitat condition and age of rice plant. In bunds of each block were put six pitfall traps with minimum distance 20 meter from each other. Ants were collected weekly from 6 until 12 weeks after planting to standardize the bunds condition. In total 22 species from 4 subfamilies of ants were recorded from this research. Iridomyrmex sp.01 and Odontoponera sp.01 are the common species which always found in each block and in different age of rice plant. There are no correlation between the distance of pitfall traps and similarity of ant species. In addition, habitat conditions surrounding rice field (block) significantly effect to the ant diversity. However, age of rice plant have no effect to the ant diversity.